Dermpath quiz: An irregularly colored papule on the back of an adolescent female - Alexandra Price; Dennis C Polley; Michael E Sabol; Dirk M Elston (Wolters Kluwer Medknow Publications, 2015)
This learning exercise challenges clinicians and dermatopathologists to consider the differential diagnosis of an unevenly colored solitary papule over the upper back of an adolescent female.